Ionic liquids as additives to enhance the extraction of antioxidants in aqueous two-phase systems - Almeida, Mafalda R.
Aqueous two-phase systems (ATPS) have been proposed as an alternative technique for the extraction, separation and/or purification of diverse biomolecules. Besides the typical polymer-salt ATPS, recently, ionic-liquid-(IL)-salt combinations have been reported to present higher extraction performances than the former systems are able to provide. Therefore, aiming at using the tailoring ability and high extraction efficiencies offered by ILs, yet with lower IL amounts, in this work novel ATPS composed of polyethylene glycol (PEG) and Na2SO4, using ILs as additives (at 5 or 10 wt%), were studied. Both the determination of the phase diagrams and their extraction efficiencies for gallic, vanillic and syringic acids were determined at 298 K. Furthermore, the effects of the molecular weight of PEG (200, 300, 400 and 600 g mol(-1)) and of the IL chemical structure were investigated. The two-phase formation ability increases with the increase of the PEG molecular weight. Moreover, the addition of low amounts of ILs is favorable for the liquid-liquid demixing. The results obtained indicate that all the antioxidants investigated preferentially partition for the PEG-rich phase although depending on the PEG molecular weight and IL employed. The addition of 5 wt% of IL leads to extraction efficiencies ranging between 80% and 99%. These results clearly demonstrate the ability of the IL to tune the polarity of the PEG-rich phase and where the IL chemical structure plays a dominant role in the extraction of phenolic acids. PEG-salt-IL ATPS represent thus an interesting advance in separation processes and open the door for a new range of IL-based extraction processes. (C) 2014 Elsevier B.V. All rights reserved.